STUDI LITERATUR: MODEL GAME BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DITINJAU DARI KONSEP DIRI SISWA - Dewi Nafla Salsabila, Anidha; Agoestanto, Arief (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
Students’ ability to understand mathematical concepts in Indonesia still tends to be low. Students’ ability to understand mathematical concepts is used as a basis for students to understand subsequent materials that are related to each other. There is a need for innovation that can help improve these abilities, one of which is the game-based learning model. This research aims to describe a game-based learning model to improve the ability to understand concepts in terms of self-concept. The research method used is a literature study that analyzes various sources related to the topic. The data analysis technique consists of four stages, namely data collection, data reduction, data display, and conclusion drawing/verification. The study results show that the game-based learning model positively affects students’ ability to understand mathematical concepts, so it can be an interactive learning innovation to improve this ability. Apart from that, self-concept also has a positive influence on students’ ability to understand mathematical concepts. Further research needs to be carried out to determine students’ ability to understand mathematical concepts, which are reviewed using self-concept and a game-based learning model directly implemented with students.